DETERMINING BARRIERS IN SUSTAINABLE REFURBISHMENT PROJECTS: COMMERCIAL BUILDING OWNER PERSPECTIVES - Masrom, Md Asrul Nasid; Abd Rahim, Mohd Hilmi Izwan; Ann, Siow Chan; Mohamed, Sulzakimin; Goh, Kai Chen; Md Yassin, Azlina (PLANNING MALAYSIA, 2017)
Existing commercial buildings in Malaysia account for one third of the total electricity consumption. They present a great opportunity for refurbishment to reduce carbon dioxide. However, sustainably refurbished commercial buildings that is Green Building Index (GBI) certified is still low. This study aims to investigate barriers that impede commercial building owners to implement sustainable refurbishment and explore ways to increase numbers of sustainable refurbishment implementation. Qualitative data were collected through semistructured interviews. The respondents were commercial building owners’ representative, who were mainly building managers. The findings indicated that higher cost of sustainable refurbishment than conventional method and lacking of sustainability awareness among Malaysian were the main barriers of sustainable refurbishment. This study will be useful in helping building owners and developers to enhance economic, social and environmental benefits of sustainable refurbishment.